A novel, community-based approach to endangered species recovery: the case of the Preble’s meadow jumping mouse (Zapus hudsonius preblei) - Knight, Heather A. L.; Beebe, Chelsea; Dick, Cory; Maiolo-Heath, Megan; Schorr, Robert (Frontiers in Conservation Science, 2025)
For more than 50 years, the United States (US) Endangered Species Act (ESA) has contributed to the protection, survival, and recovery of numerous species including gray wolves (Canis lupus), grizzly bears (Ursus arctos horribilis), whooping cranes (Grus americana), and spotted owls (Strix occidentalis). Recovery efforts by US federal agencies have largely focused on these well-known, charismatic species. As a result, lesser-known species have often been given lower priority and limited funding. An additional challenge to species recovery has been that ~ 50% of listed species have at least part of their habitats on private lands. Private landowners have sometimes viewed contributing to species recovery as an infringement on property rights. The Preble’s Meadow Jumping Mouse, Zapus hudsonius preblei, (PMJM) is a riparian specialist that serves as an indicator species for the ecological integrity of first and second-order watersheds in the Rocky Mountain region of the US. In 1998, PMJM was listed as a threatened species by the US Fish and Wildlife Service (USFWS). The listing process was prolonged by numerous lawsuits. After two different recovery teams and 21 years to produce a Recovery Plan, the USFWS recognized the need for a different approach to listed species recovery. The result, in 2019, was the establishment of the first Site Conservation Team (SCT) by the USFWS. This new SCT model uniquely combined: community-based participation and collaboration, private landowner leadership of process development and conservation action, extensive community outreach, a scientific foundation, and emphasized watershed health. The establishment of SCTs to address species conservation marked a new era taken by the USFWS. Herein we discuss the PMJM SCT located within the North Fork of the Cache la Poudre River watershed (North Fork SCT) in Northern Colorado. We identify conditions that enabled the new approach, describe the collaborative process, report how community engagement can address fears and lead to shared understanding of environmental benefits, and result in restoration actions that contribute to the species recovery. The North Fork SCT successfully nominated a recovery population nomination, developed a comprehensive conservation plan, and initiated restoration on 102 stream miles of potential habitat for approximately 4,000 PMJM individuals.